The Effect of Board Characteristics on Firm Environmental Performance - de Villiers, Charl; Naiker, Vic; van Staden, Chris J. (Journal of Management, 2011)
This study investigates the relationship between strong firm environmental performance and board characteristics that capture boards’ monitoring and resource provision abilities during an era when the natural environment and the related strategic opportunities have increased in importance. The authors relate the proxy for strong environmental performance to board characteristics that represent boards’ monitoring role (i.e., independence, CEO-chair duality, concentration of directors appointed after the CEO, and director shareholding) and resource provision role (i.e., board size, directors on multiple boards, CEOs of other firms on the board, lawyers on the board, and director tenure). The authors provide evidence consistent with both theories of board roles. Specifically, consistent with their agency theory–driven predictions, the authors find evidence of higher environmental performance in firms with higher board independence and lower concentration of directors appointed after the CEO on the board of directors. Consistent with resource dependence theory, they show that environmental performance is higher in firms that have larger boards, larger representation of active CEOs on the board, and more legal experts on the board. Their findings are generally robust to a number of sensitivity analyses. These findings have implications for managers, firms, shareholders, and regulators who act on behalf of shareholders, if they are interested in influencing environmental performance.